Development of a Videoconference-Adapted Version of the Community Diabetes Prevention Program, and Comparison of Weight Loss With In-Person Program Delivery. Issue 11 (24th April 2019) - Taetzsch, Amy; Gilhooly, Cheryl H; Bukhari, Asma; Das, Sai Krupa; Martin, Edward; Hatch, Adrienne M; Silver, Rachel E; Montain, Scott J; Roberts, Susan B
Abstract: Introduction: Effective, standardized, and easily accessible weight management programs are urgently needed for military beneficiaries. Videoconference interventions have the potential for widespread scaling, and can provide both real time interaction and flexibility in delivery times regardless of location, but there is little information on their effectiveness and acceptability. Materials and Methods: This study as part of a larger weight loss trial describes the videoconference adaption of Group Lifestyle Balance (GLB) program, a community group-based Diabetes Prevention Program intervention, and provides a comparison of weight loss and meeting attendance between in-person and videoconference delivery modes over 12 weeks in adult family members of military service members. Forty-three participants were enrolled from two military installations and received either the videoconference-adapted or an in-person GLB program in a non-randomized trial design. Differences in program attendance and percent weight lost at 12 weeks were compared by independent samples t -tests and nonparametric methods. Group differences in the percentage of weight lost over the 12-week period were analyzed using a linear mixed model. Results: All GLB intervention components were successfully delivered by videoconference with minor adaptations for the different delivery mechanism. Participant retention was 70% and 96% in the in-person and videoconference groups, respectively ( p = 0.04). Completing participants in both groups lost a significant percent body weight over the 12 week intervention ( p < 0.001) and there was no difference in percent body weight after 12 weeks of intervention (6.2 ± 3.2% and 5.3 ± 3.4% for in-person and videoconference at 12 weeks, respectively; p = 0.60). Conclusion: This study describes the first videoconference adaption of the GLB program for use in military families. Attrition was lower in the videoconference group, and there were a similar levels of weight loss in both groups regardless of delivery modality. Videoconference weight loss interventions are effective and feasible for scaling to support healthy weight management in military as well as civilian populations.